2017
DOI: 10.1161/circgenetics.116.001613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disclosing Genetic Risk for Coronary Heart Disease on Information Seeking and Sharing

Abstract: Background Whether disclosing genetic risk for coronary heart disease (CHD) to individuals influences information seeking and information sharing is not known. We hypothesized that disclosing genetic risk for coronary heart disease (CHD) to individuals influences information seeking and sharing. Methods and Results The Myocardial Infarction Genes (MI-GENES) study randomized participants (n=203) aged 45–65 years who were at intermediate CHD risk based on conventional risk factors and not on statins, to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Other methods may provide additional useful clinical information for dyslipidaemias. These techniques include: (1) proteomic methods, whereby protein expression is assessed at the cell or tissue level to indirectly evaluate gene expression; (2) metabolomics, which refers to the concurrent assessment of small molecule metabolites from serum or tissue samples to indirectly evaluate in a targeted manner variations in gene products involved in intermediate biochemical pathways or in drug metabolism; 20,21 and (3) genome-wide transcriptome analysis of RNA expression (e.g., RNASeq) that can be further used to assess gene expression and patterns of alternative RNA splicing within a cell or tissue. 22 Epigenetics is increasingly recognised as affecting genotype-phenotype relationships.…”
Section: Other Advanced Genetic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods may provide additional useful clinical information for dyslipidaemias. These techniques include: (1) proteomic methods, whereby protein expression is assessed at the cell or tissue level to indirectly evaluate gene expression; (2) metabolomics, which refers to the concurrent assessment of small molecule metabolites from serum or tissue samples to indirectly evaluate in a targeted manner variations in gene products involved in intermediate biochemical pathways or in drug metabolism; 20,21 and (3) genome-wide transcriptome analysis of RNA expression (e.g., RNASeq) that can be further used to assess gene expression and patterns of alternative RNA splicing within a cell or tissue. 22 Epigenetics is increasingly recognised as affecting genotype-phenotype relationships.…”
Section: Other Advanced Genetic Testsmentioning
confidence: 99%
“…Individuals with high genetic risk were more likely to remain on their statins than those at low genetic risk or those who were not informed of their genetic profile. 20…”
Section: Impact On Patientsmentioning
confidence: 99%
“…The study found no effect of GRS on lifestyle behaviors (e.g., dietary fat intake or physical activity levels), but it also found no increase in patient anxiety 34 , 36 . The research group reported in separate studies that patients who received the GRS had slightly higher perceived personal control and genetic counseling satisfaction (37) and that patients who received a GRS were more likely at 6 months post-disclosure to have sought out additional information about coronary heart disease (CHD) and genetic risk factors of CHD than patients who received a CRS (38) . Although the study was limited by lack of physician blinding and included genetic information from only 11 SNPs, it provided an important example of a GRS affecting clinical measures, underscoring the potential of such information to change practitioner prescribing behavior.…”
Section: Spotlight On Precision Medicine In a Common Cvd: Cad And Carmentioning
confidence: 99%
“…Therefore, the impact of genomic information naturally extends beyond a healthcare encounter–through conversation it travels from the patient, out to their extended family and to people who are not yet patients. Such people could be considered a type of ‘patient in waiting’ 21 ; we don’t yet know where and how they seek out information and meaning, but it is likely they look to the media 22 , popular culture 23 and the Internet 24 for insight. It is important when assessing how people respond to genetic information to ensure that ’the public’ is not envisioned as a singular, unified entity.…”
Section: Introductionmentioning
confidence: 99%